Implications of Intravenous and Inhaled Amikacin Breakpoint Reporting for Mycobacterium avium Complex Pulmonary Isolates - Christian M. Gill; Robin Chamberland; Getahun Abate (Pathogens, 2025)
The treatment of Mycobacterium avium complex (MAC) remains a clinical challenge as multidrug regimens are needed and may be limited by treatment-related toxicity. The Clinical and Laboratory Standards Institute (CLSI) endorses breakpoints for several agents used for MAC infection treatment. Amikacin has distinct breakpoints for intravenous (IV) therapy and inhaled therapy using amikacin liposome inhalation suspension (ALIS) for MAC pulmonary disease. The purpose of the present retrospective cohort study of MAC pulmonary isolates was to assess the number of amikacin non-susceptible isolates by the IV breakpoints that remain susceptible to the inhaled breakpoints. One isolate per patient per year was assessed and susceptibility was described for amikacin IV, amikacin inhaled, clarithromycin, moxifloxacin, and linezolid per the CLSI. Of the 218 isolates, 94% [204/218] tested as susceptible to amikacin per the IV breakpoints compared with 99.5% [217/218] to the inhaled breakpoints. Of the amikacin IV non-susceptible isolates, 93% [13/14] were susceptible by the inhaled breakpoints. For comparison, clarithromycin was the next most active agent followed by moxifloxacin and linezolid with 97% [211/218], 82% [178/218], and 66% [143/218] of isolates testing as susceptible to each, respectively. These data highlight the importance of laboratories to report both the IV and inhaled amikacin interpretive criteria so that clinicians do not disregard potential therapeutic options for the treatment of MAC pulmonary disease.